A mitochondria-targeted ratiometric fluorescence probe for detection of SO2 derivatives in living cells. (November 2020) - Sun, Wan-Xue; Li, Na; Li, Zhang-Yi; Yuan, Yu-Chang; Miao, Jun-Ying; Zhao, Bao-Xiang; Lin, Zhao-Min
Abstract: In this report, a mitochondria-targeted probe based on an efficient platform constructed by pyridinium-coumarin and 2-dicyanomethylene-3-cyano-4, 5, 5-trimethyl-2, 5-dihydrofuran (TCF) with high selectivity and sensitivity toward SO2 derivatives was presented. As far as we know, pyridinium-coumarin is first used as a donor moiety to construct a FRET system. Compared with our previous work, it showed better solubility, higher biocompatibility and faster response speed. It also presented low detection limit (80.5 nM), excellent energy transfer efficiency (98.2%) and low cytotoxicity. Moreover, the probe could detect exogenous and endogenous bisulfite in living cells as well as in mitochondria successfully. Graphical abstract: Image 1 Highlights: A new FRET-based ratiometric fluorescence probe (named PCPT) for HSO3 − /SO3 2− was developed. Probe PCPT showed a large pseudo Stokes shift (213 nm), high selectivity, sensitivity. Probe PCPT could target well mitochondria in cell image. Probe PCPT could image endogenous HSO3 − /SO3 2− in HepG2 cells.